Safety confessions as the main problem in the system state and religious policy (Journal of Philosophy Culture and Political Science, 2018)
In this article,the author has donework on the analysisof oneof the main tasksof state-religious policy. This analysiswas carried outon the example ofthe Republic of Kazakhstanin the context ofmulti-confessionalsociety. The current situationrequiresthe governmentproperunderstanding ofthe roles and responsibilitiesof state-confessional relations for theregulationof ethnic and religiouspolicies andthe country’s security. It describesthe role of religionand its institutionsin the socio-political life of Kazakh societyin modern times.Describing thereligious situationin the country, the spread of Islamsays thatthere is no basisfor thepoliticization of Islamand its transformation intoa serious political force, as is the casein a number ofIslamic countries, as well as in some regions ofRussia, wherethe core ofthe political oppositionoftenmakeradicalproponentsof Islamicfundamentalism.Key words: Confession, security, state-confessional relations, Kazakhstan, religious organizations, secular, faith.